2012
DOI: 10.1590/s1809-98232012000100015
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados a quedas em idosos residentes em um bairro de Fortaleza, Ceará

Abstract: A queda é uma das consequências mais graves do envelhecimento, sendo reconhecida como importante problema de saúde pública. A pesquisa teve como objetivo investigar aspectos relacionados à ocorrência de quedas em idosos. Participaram do estudo 50 idosos, do bairro Cidade 2000, em Fortaleza-CE, sendo 64% do gênero feminino. Para a coleta de dados foi utilizado um questionário. Observou-se que 42% dos idosos apresentaram, no mínimo, um episódio de queda nos últimos dois anos, dos quais 19% se encontravam entre 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1
15

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 30 publications
(39 reference statements)
2
12
1
15
Order By: Relevance
“…More than half of patients included in this study suffered recurrent falls, agreeing with other results found in literature [20,21]. The presence of a history of falls is strongly associated with the occurrence of further declines, evidencing scientifically [22].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…More than half of patients included in this study suffered recurrent falls, agreeing with other results found in literature [20,21]. The presence of a history of falls is strongly associated with the occurrence of further declines, evidencing scientifically [22].…”
Section: Discussionsupporting
confidence: 90%
“…The home environment is very conducive to the occurrence of falls, which may cause tripping on shoes, furniture, clothing, carpets, and slips into the kitchen floors and bathrooms, for example, especially when the elderly performs cleanup tasks [26]. However, the decrease in the home it is a relatively simple event to be avoided, whereas reorganization preventive measures can be adopted [20]. On the street environment, it is considered a risk factor for falls therefore has uneven sidewalks, favoring stumbling [27].…”
Section: Discussionmentioning
confidence: 99%
“…Compreendem uma intercorrência de maior importância para a pessoa idosa, causando desde pequenas escoriações até fraturas diversas em membros, traumatismos cranianos e fraturas de quadril, resultando muitas vezes em óbito. 10,11 Diante da seriedade desse agravo para a saúde pública e da escassez de dados na literatura sobre o idoso vítima de trauma por queda na comunidade admitido em unidade de alta complexidade, verificou-se a importância de conhecer o perfil dessa população, além das complicações e do desfecho decorrentes do evento traumático. Assim, essas informações poderiam subsidiar a formulação de protocolos de atendimento a esses idosos, e ações públicas preventivas mais eficientes poderiam ser adotadas, já que esse tipo de trauma predominantemente tem causas evitáveis.…”
Section: Introductionunclassified
“…The risk of falling increases with age. Studies conducted in different countries addressed falls among elderly people, and detect annual frequencies ranging from 6.5% to 42% 2,3 .About 30% of persons over 65 years old and 50% of those over 80 suffer at least an annual fall worldwide 4 . Falls are major public health concern for older adults, and with the increasing numbers of elderly population worldwide, research are critically needed for establishing effective policies to reduce risk 5 .…”
Section: Introductionmentioning
confidence: 99%